Inhibitors of Human Immunodeficiency Virus Type 1 Reverse Transcriptase Target Distinct Phases of Early Reverse Transcription - Hooker, C. William (American Society for Microbiology, 2001)
Early HIV-1 reverse transcription can be separated into initiation and elongation phases. Here we show, using PCR analysis of negative-strand strong-stop DNA [(−)ssDNA] synthesis in intact virus, that different reverse transcriptase (RT) inhibitors affect distinct phases of early natural endogenous reverse transcription (NERT). The effects of nevirapine on NERT were consistent with a mechanism of action including both specific and nonspecific binding events. The nonspecific component of this inhibition targeted the elongation reaction, whereas the specific effect seemed principally to be directed at very early events (initiation or the initiation-elongation switch). In contrast, foscarnet and the nucleoside analog ddATP inhibited both early and late (−)ssDNA synthesis in a similar manner. We also examined compounds that targeted other viral proteins and found that Ro24-7429 (a Tat antagonist) and rosmarinic acid (an integrase inhibitor) also directly inhibited RT. Our results indicate that NERT can be used to identify and evaluate compounds that directly target the reverse transcription complex.